Разрушение керамики на основе ZrO₂ при механическом воздействии - Милявский, В.В.; Акопов, Ф.А.; Вальяно, Г.Е.; Лукин, Е.С.; Попова, Н.А.; Бородина, Т.И.; Валуев, А.В.; Ананьев, С.Ю.; Боровкова, Л.Б.; Зиборов, В.С. (Физика и техника высоких давлений, 2013)
Исследовано влияние температуры изохронных отжигов на эволюцию структуры и механические свойства йодидного титана, подвергнутого интенсивной пластической деформации (ИПД) по схеме осадка−выдавливание−волочение. Показано, что наиболее резкие изменения структуры и свойств материала наблюдаются в довольно узком интервале температур вблизи 350°С. Вивчено вплив температури ізохронних відпалів на еволюцію структури та механічні властивості йодидного титану, що пройшов інтенсивну пластичну деформацію (ІПД) за схемою осадка−видавлювання−волочіння. Показано, що найбільш різкі зміни структури й властивостей матеріалу спостерігаються у досить вузькому інтервалі температур поблизу 350°С. Titanium and its alloys are widely used in engineering. Pure titanium possesses high biologic compatibility, and provided its strength is increased, it holds much promise for medical implants. Its properties can be optimized by forming ultra-fine grain structure through severe plastic deformation (SPD) combined with programmed heat treatment. The present investigation was aimed at studying of the effect of isochronous annealing temperature on microstructure evolution and mechanical properties of pure titanium that had been subjected SPD by the upsetting−extrusion−drawing route. Iodine titanium was used for the research. After SPD-treatment, the titanium samples were studied in uniaxial tension in both initial and annealed (Tann = 150−550°С, t = 1 h) states. Optical and electron microscopy were applied to study the structure of the samples. Microhardness Нμ of all the samples was measured. The sample state effects on stress-strain curves and their parameters, σ0.2, σb, σp, δр, δ, ψ, as well as Нμ, were investigated. Correlation between the parameters and the microstructure features was traced. It was shown that the applied SPD route, being a combination of simple processes, i.e. upsetting, extrusion, drawing, efficiently refines grains in the high purity titanium and permits the microstructure state of 150 nm in the mean grain size to be obtained. A required combination of strength and plastic properties of SPD high purity titanium can be realized by optimizing annealing temperature near 350°С and varying the heat treatment time.